SPEEK/ZnO Nanocomposite Modified Gold Electrode for Electrochemical Detection of Dopamine. Issue 12 (2nd September 2020) - Fayemi, Omolola E.; Baskar, R.; Adekunle, Abolanle S.; Sherif, El‐Sayed M.; Ebenso, Eno E.
Abstract: Drop casting method was used for the fabrication of modified electrode of sulphonated polyether ether ketone/zinc oxide (SPEEK/ZnO) nanocomposite on gold electrode for electrochemical oxidation of dopamine. The SPEEK/ZnO nanocomposites were characterized by using fourier transform infrared (FT‐IR), and Uv‐Vis, while the surface morphology was assessed by scanning electron microscopy (SEM). Elemental composition was determined using Electron dispersive spectroscopic (EDS). The electrocatalysis of dopamine at gold electrode (Au) modified with SPEEK/ZnO nanocomposites in 0.1 M phosphate buffer solution (PBS at pH 7) was examined using cyclic voltammetry. The result obtained at Au/SPEEK/ZnO modified electrode was compared with those obtained at the bare Au and Au/SPEEK nanocomposite modified electrodes. It was found that the ZnO nanoparticles increased the electroactivity of SPEEK towards dopamine oxidation. The Au/SPEEK/ZnO electrode exhibited good linear plot for the concentration range from 5.4×10 −13 M to 1.9×10 −9 M, with a limit of detection and sensitivity values of 0.89 nM and 18.47 μA mM −1 cm −2 respectively. The modified Au/SPEEK/ZnO also gave distinct separated peaks for dopamine and ascorbic acid in a mixture of both analytes. Also a satisfactory stability result was recorded for the Au/SPEEK/ZnO modified electrode when stored at room temperature for several days. The electrode was successfully used to assay dopamine in real life sample. Abstract :